Antecedent hypertension and myocardial injury in patients with reperfused ST-elevation myocardial infarction. Issue 1 (January 2017) - Reinstadler, Sebastian; Stiermaier, Thomas; Eitel, Charlotte; Saad, Mohammed; Metzler, Bernhard; de Waha, Suzanne; Fuernau, Georg; Desch, Steffen; Thiele, Holger; Eitel, Ingo
Abstract Background Antecedent hypertension is associated with poor outcome in patients with ST-elevation myocardial infarction (STEMI). Whether differences in myocardial salvage, infarct size and microvascular injury contribute to the adverse outcome is unknown. We investigated the association between antecedent hypertension and cardiovascular magnetic resonance (CMR) parameters of myocardial salvage and damage in a multicenter CMR substudy of the AIDA-STEMI trial (Abciximab Intracoronary versus intravenously Drug Application in ST-elevation myocardial infarction). Methods We analyzed 792 consecutive STEMI patients reperfused within 12 h after symptom onset. Patients underwent CMR imaging for assessment of myocardial salvage, infarct size and microvascular obstruction within 10 days after infarction. Major adverse cardiac events (MACE) were recorded at 12-month follow-up. Results Antecedent hypertension was present in 540 patients (68 %) and was associated with a significantly increased baseline risk profile (advanced age, higher body mass index, higher incidence of diabetes, hypercholesterolemia, previous angioplasty and multivessel disease, p  < 0.001 for all). MACE were more frequent in patients with hypertension as compared to patients without hypertension (45 [8 %] vs. 8 [3 %], p  < 0.01). Antecedent hypertension remained an independent predictor of MACE after multivariate adjustment (hazard ratio 3.42 [confidence interval 1.45–8.08], p  < 0.01). There was, however, no significant difference in the area at risk, infarct size, myocardial salvage index, extent of microvascular obstruction, and left ventricular ejection fraction between the groups (allp  > 0.05). Conclusion Despite a higher rate of MACE in contemporary reperfused STEMI patients with antecedent hypertension, there was no difference in reperfusion efficacy, infarct size and reperfusion injury as visualized by CMR. Trial registration NCT00712101 .